INDONESIA DALAM PENERAPAN HUKUM BERDASARKAN ALIRAN MONISME, DUALISME DAN CAMPURAN - Veriana Josepha B. Rehatta (SASI, 2016)
Countries in the world in the activity always in touch and relate with other countries. This causes the applicable national law a country will always be associated also with international law. It spawned two big flow of the relationship between national law and international law, namely the flow of monism sees both national law and international law are two aspects of the same from one system, and the flow of dualism considers that international law and national laws is a two fields laws are different and independent from one another. both monism and dualism, each has perceived flaws could not answer development issues at present, then the birth of a new legal theories such as the theory of transformation, the delegation theory and the theory of harmony. According to the theory of transformation, the rules of international law to be valid and honored as national norms have to go through the transformation process or over forms, either formally or substantially. Meanwhile, according to the theory of the delegation, the implementation of international law left to the states or the national law of each. So the problem of implementation was delegated to national law. And according to the theory of international law and the harmonization of national law must be interpreted in such a way that between them there was harmony. it was clear that Indonesia as part of the international community can not escape from the application of international law and also can not rule out the positive law or domestic law. So based on the spirit of nationality and legal ideals (recht idee) Indonesia, then Indonesia following the flow of mixture between Monism and dualism in this harmonization, but harmonization is hoped that coordinate with each other harmonization